Resident’s Perspective on Developing Community-Based Tourism – A Qualitative Study of Muen Ngoen Kong Community, Chiang Mai, Thailand - Lo, Yu-Chih; Janta, Pidpong (Frontiers in Psychology, 2020)
Community-Based Tourism (CBT) has been presented as an alternative to sustaining tourism development in developing countries. This tourism model offers local residents an opportunity to manage natural and cultural resources in order to promote the local economy and generate greater benefits. The objective of the study is to investigate the benefits and challenges of CBT as well as solutions to address identified shortcomings by studying Muen Ngoen Kong community in Chiang Mai, Thailand. In order to achieve these objectives, qualitative methods, field observations, and interviews were employed, and qualitative data were analyzed using thematic analysis. The results of the field observation and interview data from local residents were reported, analyzed, and discussed. To practice CBT, the findings indicated that several challenges had been experienced in the implementation of CBT, including conflict over resource ownership and benefit leaking, financial issues, and problems of community participation. However, an abundance of tourism resources and security related concerns were identified as benefits of CBT in the area. In close collaboration with government agencies, product development was recommended to create a unique condition for CBT and address the shortcomings. It is crucial to involve local residents, empower the local community, conserve and cultivate cultural resources, and, finally, to maintain the overall sustainability of tourism resources.